2019
DOI: 10.1111/rda.13467
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of minerals in the canine prostatic fluid

Abstract: Current knowledge about the composition of the prostate fluid in healthy male dogs is limited and restricted to small case numbers. Furthermore, published data often vary significantly regarding sample processing and analytical methods. Therefore, we aimed to provide data on the composition of electrolytes and minerals in the canine prostatic fluid in a larger population (n = 30 dogs/samples) and to compare these results with the existing literature. Concentrations of sodium, potassium and copper analysed in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Total Ca did not show variations before and during the treatment with OA. These results are in agreement with data on prostatic fluid total Ca concentrations reported by Umbach et al(2019). To our knowledge, only two studies showed higher values of total Ca in canine prostatic fluid (Aquino‐Cortez et al., 2017; Quinn et al., 1965), although centrifugation speed and time were higher (4000 & 1840 g for 30 and 20 min) when compared to values of 1098 and 700 g for 10 and 5 min in our study (and the study of Umbach et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Total Ca did not show variations before and during the treatment with OA. These results are in agreement with data on prostatic fluid total Ca concentrations reported by Umbach et al(2019). To our knowledge, only two studies showed higher values of total Ca in canine prostatic fluid (Aquino‐Cortez et al., 2017; Quinn et al., 1965), although centrifugation speed and time were higher (4000 & 1840 g for 30 and 20 min) when compared to values of 1098 and 700 g for 10 and 5 min in our study (and the study of Umbach et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…These results are in agreement with data on prostatic fluid total Ca concentrations reported by Umbach et al (2019). To our knowledge, only two studies showed higher values of total Ca in canine prostatic fluid (Aquino-Cortez et al, 2017;Quinn et al, 1965), although centrifugation speed and time were higher (4000 & 1840 g for 30 and 20 min) when compared to values of 1098 and 700 g for 10 and 5 min in our study (and the study of Umbach et al, 2019). This might mean that higher centrifugation speeds for longer times might break sperm membrane releasing intracellular calcium (Rijsselaere et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…In one retrospective study [139], the postoperative survival time (time between operation and death) was 231 days (median; range: 24-1255 days). In the evaluated studies, ureter-urethral anastomoses (14), cysto-urethral anastomoses (9), anastomoses between ureter and colon (1), and anastomoses between urinary bladder neck and pelvic part of the urethra were described (1). The dogs in addition received mitoxantrone, NSAID, metronomic thalidomide, cyclophosphamide, piroxicam, carboplatin, and/or deracoxib.…”
Section: Therapymentioning
confidence: 99%
“…The canine prostate secretion is a transport medium among others for passive transportation of the spermatozoa into the uterus during ejaculation. The prostate secretions furthermore influence the motility and function of the semen cells; the exact composition and many functions are not yet known and vary dependent on the laboratory and the analysis method used [1]. The composition of mineral nutrients, as well as the amount of cholesterol, albumin [2], zinc-binding proteins [3], fertility-associated proteins like osteopontin [4], the antioxidative capacity [5], and many more have been examined.…”
Section: Introductionmentioning
confidence: 99%